Minimally Invasive Thoracic Surgery in Pediatric Patients: The Taiwan Experience. (30th May 2013) - Huang, Yu-Kai; Chou, Chieh; Li, Chung-Liang; Chiu, Hui-Gin; Chang, Yu-Tang
Abstract : Minimally invasive technology or laparoscopic surgery underwent a major breakthrough over the past two decades. The first experience of thoracoscopy in children was reported around 1980 for diagnosis of intrathoracic pathology and neoplasia. Up until the middle of the 1990s, the surgical community in Taiwan was still not well prepared to accept the coming era of minimally invasive surgery. In the beginning, laparoscopy was performed in only a few specialties and only relatively short or simple surgeries were considered. But now, the Taiwan's experiences over the several different clinical scenarios were dramatically increased. Therefore, we elaborated on the experience about pectus excavatum: Nuss procedure, primary spontaneous hemopneumothorax, thoracoscopic thymectomy, and empyema in Taiwan.